The role of genetic factors in microtia: A systematic review - Indri Lakhsmi Putri, Indri
Abstract Background: Microtia is a congenital malformation of the outer ears caused by improper embryonic development. The origin of microtia and causes of its variations remain unknown. Because of the lack of clarity regarding the role of genetic variables in microtia, we conducted a systematic review to qualitatively identify the genes most important in the development of microtia to provide an up-to-date review. Methods: Using six search engines, we searched all published studies related to the genetic factors of isolated microtia and syndromic microtia. The identified publications were screened and selected based on inclusion and exclusion criteria by the authors and assessed for methodological quality using the Joanna Briggs Institute (JBI) critical appraisal tools. We found 40 studies, including 22 studies on syndromic microtia and 18 studies on isolated microtia. Data extraction of each study was arranged in tabulation for syndromic and isolated microtia. The extracted data were: first author’s surname, year of publication, country of origin, study design, sample characteristic and gene assessed. Results: After the data were extracted, analyzed, and reviewed, the most common gene suspected to be involved in isolated microtia was Homeobox A2 (HOXA2, 12.1%). Conversely, in syndromic microtia, the two most common genes supposed to play a role were Fibroblast Growth Factor 3 (FGF3, 47.2%) and Treacher–Collins–Franceschetti syndrome 1 (TCOF1, 30.2%). From the studies, the three most prevalent genes associated with microtia were HOXA2 (10%), FGF3 (8.4%), and TCOF1 (5.4%). In syndromic microtia, the most common mutation types were deletion in TCOF1 (46.9%) and missense and deletion in FGF3 (both 38%), and in isolated microtia, the most common mutation type was silent in HOXA2 (54.2%). Conclusions: In summary, genetic factors are involved in microtia; thus, molecular analysis is strongly advised.